Production of Acalypha wilkesiana seedlings using stem cuttings - Fernandes Sarkis, Leonardo; Fernandes Guareschi , Roni; Almeida dos Santos, Camila; Sebastião de Paula Araujo, João; dos Santos Rosa de Oliveira, Víctor; Cândido da Silva Rodrigues, Gustavo (Comunicata Scientiae, 2022)
The objective of this work was to evaluate the rooting of cuttings of Acalifa (Acalypha Wilkesiana) with different concentrations of indolbutyric acid (IBA). The matrix plant from which the cuttings were taken, is planted as a hedge and located at the biology institute of the Federal Rural University of Rio de Janeiro in the city of Seropédica-RJ. The experimental design was completely randomized, in a 3x3 factorial, with three different concentrations of IBA (0, 1000 and 2000 mg L-1 or 0, 2000 and 4000 mg L-1 for 15 seconds) and three types of cuttings (herbaceous, semi-woody and woody), with three replications and ten cuttings per plot. The experiments were carried out at two different times, namely: autumn and winter / spring. The following were evaluated: percentage of live cuttings, rooted, with callus and sprouting, number of roots per cut, length of the largest root. Acalypha wilkesiana can be propagated by stem cuttings, whether woody, semi-woody or herbaceous cuttings. However, herbaceous cuttings have a lower percentage of survival and rooting. Also, is a species of easy rooting through cutting of stems, dispensing with the use of AIB. Stems collected in the autumn period yield greater efficiency and productivity in the propagation of cuttings by cuttings.